Cultura jurídica e tradição : o conflito entre os usos e costumes tradicionais moçambicanos e a herança jurídica dos colonizadores - Cuco, Arcênio Francisco (2013)
This research sought to understand the conflict between practices and traditional usages and the colonial legal culture within the current social dynamics of Mozambique, leading to the following question: how can the conflict between usages and traditional practices and the colonial legal culture embedded in the contemporary social dynamics of Mozambique can be understood? It addresses a case of conflict between the state justice system and a traditional practice called muáwelo in the northern of Nampula Province, concretely in Nacala-Porto city. The main objective was to analyze the current Mozambican social context, seeking to understand the inducing factors of the conflicts between groups in favor of colonial legal rules and the traditional usages. Furthermore, we described the forms of articulation (current) between the justice system and traditional communities in Mozambique and analyzed some practical cases of the present conflicts between traditional practices and Mozambicans usages and the legal culture. However, the work was divided into two parts. The first part consists of two chapters, that gives a brief history of Mozambique, emphasizing in to issues relating to their people, since the Portuguese colonists arrival of and the effective occupation of the territory of Mozambique. The research also analyzes how the colonists faced the local people and their practices and traditional usages, cultural clashes and the introduction of the colonial legal system and its impact on ways of solving conflicts between the local people.The second part consists of a chapter. This part addresses the issue of conflict between practices and traditional usages and legal culture transmitted by settlers from discussing the case of muáwelo previously referenced.